Employee Property Rights on Social Media Accounts in Bankruptcy Proceedings - Jintcharadze, Nukri (European Scientific Journal, ESJ, 2023)
The popularity of social media has erased legal ambiguity regarding ownership rights in social media accounts. In particular, does an employee have property rights to social media accounts in bankruptcy proceedings, or is a social media account considered the property of the enterprise? The article aims to assess ownership issues of social media accounts by relevant Georgian and international legislation in force. Especially, the article, through comparative analyses, will examine if all social media accounts should automatically be considered as property. Moreover, the article discusses the purposes of social media accounts: personal, business, and mixed usage and their ascertainable value through the analysis of national and international case law. Besides the challenging issues mentioned above, the article distributes a study on distinguishing "account" and "digital content" in social media. Accordingly, the article examines the crucial question that social media accounts should be included in the insolvency estate as property and lines between ownership rights of the enterprise and the employee should be drawn case by case, according to concrete social media and legislative rules.